English for Specific Purposes in Tourism Higher Education: Trends, Gaps, and Future Directions in Curriculum Design - Achmad Leofaragusta Kurniawan Komerendo; Herman Herman; Muhammad Bambang Purwanto (Journal of Advanced Multidisciplinary Research, 2025)
English for Specific Purposes (ESP) has become a crucial component in tourism higher education as the industry increasingly demands graduates who are communicatively competent, professionally confident, and interculturally aware. This article aims to provide a descriptive analysis of current trends, identify key gaps, and propose future directions in ESP curriculum design within tourism higher education. Using a descriptive qualitative approach, this study synthesizes relevant literature on ESP, tourism education, and curriculum development to map prevailing pedagogical practices and conceptual challenges. The findings indicate that contemporary ESP tourism curricula have shown a positive movement toward speaking-oriented, task-based, and performance-driven instruction that reflects the needs of workplace communication. However, significant gaps persist between students’ linguistic competence and their readiness to perform professional communication in authentic tourism contexts. These gaps are primarily attributed to the limited integration of industry-based service scenarios, psychological readiness factors such as confidence and willingness to communicate, and the development of intercultural competence. The discussion highlights the need to reconceptualize ESP tourism not merely as linguistic pedagogy, but as professional communication pedagogy that emphasizes service-oriented discourse, authentic tasks, and learner readiness. This article concludes that a holistic ESP tourism curriculum, integrating linguistic, psychological, cultural, and professional dimensions, is essential to bridge the gap between classroom learning and real-world tourism communication. The study offers conceptual implications for curriculum designers and educators and recommends future empirical research across diverse local and global tourism contexts to further validate and refine ESP tourism curriculum models.